Risk governance and financial performance of public commercial banks of the OECD - Malik Muddassar (Virtus Interpress, 2025)
This study investigates a relationship between risk governance characteristics and financial performance in public commercial banks across the Organization for Economic Co-operation and Development (OECD) countries. Drawing on the upper echelons theory (UET) (Hambrick & Mason, 1984), it hypothesizes a positive relationship between risk governance characteristics and financial performance. An econometric model is applied to a comprehensive dataset of bank-director years spanning from 2001 to 2019. The empirical findings provide robust evidence supporting a positive and statistically significant relationship between risk governance characteristics of bank directors and financial performance in public commercial banks (Adams et al., 2010). Banks with stronger risk governance structures and characteristics exhibit significantly higher financial performance outcomes. The implications of this study are twofold. Firstly, it highlights the crucial role of efficient and effective risk governance practices in boosting financial performance in the banking sector. The research suggests that banks can greatly benefit from robust risk management systems, enhanced board independence, and expanded director expertise. Additionally, the findings provide actionable guidance for bank directors, regulators, and policymakers in shaping risk governance frameworks and policies. These insights indicate that effective risk governance indirectly improves financial performance and bank stability.